Targeting a pathogenic cryptic exon that drives HLRCC to induce exon skipping - Siddhardha S. Maligireddy; Mariana D. Mandler; Judith C. Lunger; Madeline Yuen; Sneha Kulkarni; Alexendar R. Perez; Christina M. Fitzsimmons; Daniel R. Crooks; Raj Chari; W. Marston Linehan; Pedro J. Batista (Molecular Therapy: Nucleic Acids)
Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) is an autosomal dominant cancer predisposition syndrome driven by the loss of fumarate hydratase (FH) activity. Recently, we identified a pathogenic variant in intron 9 of the FH gene that disrupts splicing by creating a novel splice acceptor site, resulting in the aberrant inclusion of a cryptic exon. Inclusion of the cryptic exon introduces a premature termination codon, leading to loss of FH activity. To restore FH expression, we sought to identify strategies to drive exclusion of the cryptic exon from the mature mRNA. To this end, we generated a minigene GFP reporter system that recapitulates the splicing defect observed in patients. We employed CRISPR-Cas9-mediated genome editing and antisense oligonucleotides (ASOs) to modulate splicing and demonstrated that both strategies can successfully promote skipping of the cryptic exon in a reporter cell line. Furthermore, we were able to show that ASOs can be used to shift the balance between the FH mRNA isoforms originated from the reference and the variant allele in patient-derived fibroblasts using ASOs. These findings support the potential for splicing modulation as a therapeutic approach for HLRCC-associated non-coding loss-of-function mutations in FH.